Efficacy of Andrographis paniculata spray in acute pharyngitis: A randomized controlled trial - Okonogi, Risa; Thampanya, Vich; Okonogi, Siriporn (Drug Discoveries & Therapeutics, 2023)
Acute viral pharyngitis is a self-limited disease but the symptoms, a sore throat in particular, can affect one's quality of life. Medicine for symptom relief is the main treatment. Recently, many studies have shown that Andrographis paniculata was efficacious in treating many diseases, including upper respiratory infections. However, adverse reactions to systemic intake are a concern. Therefore, A. paniculata spray is intended to reduce systemic adverse reactions and provide patients with more comfort as its local use. This randomized, double-blind study enrolled 60 adult patients with acute viral pharyngitis. All patients were asked to score the severity of symptoms including a sore throat, difficulty swallowing, and coughing using an 11-point numeric rating scale from 0 to 10. A physical examination was performed to score the severity of erythematous and swollen mucosa using a 0-3 score (0 = no, 1 = mild, 2 = moderate, and 3 = severe). The patients were randomized to receive treatment with either an A. paniculata spray or a positive control chamomile spray. Results revealed a significant reduction in the severity of all signs and symptoms in both groups (p < 0.05). The duration of treatment response in the A. paniculata spray group was 1.9 ± 0.7 days compared to 2.5 ± 1.2 days in the chamomile spray group (p = 0.049). No adverse events were noted in either group. A. paniculata spray is safe and highly efficacious in treating acute viral pharyngitis and can reduce symptoms more rapidly than a positive control spray.